THE ‘SIMPELAKU’ EXPERIENCE: ANALYZING SERVICE QUALITY AT THE POPULATION AND CIVIL REGISTRATION OFFICE IN CIANJUR REGENCY - Zahra Laisha Anwar; Rizki Hegia Sampurna; Tuah Nur (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2025)
This study aims to analyze the quality of services of the Integrated Population Administration Service Management Information System (SIMPELAKU) at the Cianjur Regency Population and Civil Registration Office; SIMPELAKU is a public service innovation to make it easier for people to access population and civil registration document recording services without having to come directly to the office. The research method used is quantitative with a descriptive approach. The research sample was 100 people from Cianjur Regency who submitted population documents through SIMPELAKU. This study uses the theory of Zeithaml, Parasuraman & Berry (1988: 12-40) which has five dimensions, namely tangibles, reliability, responsiveness, assurance and empathy. The results showed that the service quality of DKPS Cianjur Regency was good, with tangibles having the lowest contribution of 17.52. The indicator of officers responsible for providing services received the highest average of 4.59, while the indicator of office facilities suitable for use received the lowest average of 4.33.